The Relationship between Trust and Family Empowerment to Prevent Transmission of Pulmonary Tuberculosis - Nirmala Kusumaningrum Sunaryo; Joni Haryanto; Florentina Sustini (Alta Dharma Publisher, 2020)
Tuberculosis (TB) is infectious diseases directly caused by TB bacteria (Mycobacterium tuberculosis). Tuberculosis has been around for thousands of years and remains a significant issue of global health issues. This study aimed to analyze the relationship between trust and family empowerment in preventing pulmonary TB transmission. A cross-sectional design was applied in this study. The results showed that there was a relationship between trust and family empowerment to avoid the transmission of pulmonary TB (p-value = 0.028). Health workers needed to concern about this transmission of diseases and educated of family members on the transmission of pulmonary TB.